El componente teórico en la producción científica / ABSTRACT Although scientific production is a product, is also a process; achieve more systematic, relevance, scientific approach and organization become key for the research that represents true contributions and advances in science, from the research whatever. Here, within this process of producing science, there are several components; one of them is the theoretical component, which represents one of the pillars of scientific development. The purpose of this paper is to present a descriptive and explanatory view of the role of theory in scientific production component; achieve notions establish logical and reasonable theory of why we employ in our investigations, or even - more - why or submit to generate contrast, is one of the great journeys that every researcher must perform. Hence, for a researcher to understand the scientific processes must recognize the purpose and value of theory in research, he is the same one that generates or has a good chance to evaluate. - Leal, Lionel; Rincón, Oriana (Impacto Científico, 2020)
Resumen Aunque la producción científica supone un producto, es a la vez un proceso; lograr la mayor sistematicidad, relevancia, cientificidad y organización se convierten en aspectos clave para que las investigaciones lleguen a representar verdaderos aportes y avances para la ciencia, desde la línea de investigación que sea. En este sentido, dentro de este proceso de producir ciencia, se encuentran varios componentes, siendo uno de ellos el componente teórico, el cual representa uno de los pilares del desarrollo científico. El propósito de este trabajo es presentar una visión descriptiva del papel del componente teórico en la producción científica; lograr establecer nociones lógicas y razonables del por qué empleamos teoría en nuestras investigaciones, o más aun por qué la generamos o sometemos a contraste, es una de las grandes travesías que todo investigador debe realizar. De allí que para que un investigador entienda los procesos científicos debe reconocer el propósito y valor de la teoría dentro de la investigación, sea la que él mismo genere o aquella que a bien tenga la oportunidad de evaluar. ABSTRACT Although scientific production is a product, is also a process; achieve more systematic, relevance, scientific approach and organization become key for the research that represents true contributions and advances in science, from the research whatever. Here, within this process of producing science, there are several components; one of them is the theoretical component, which represents one of the pillars of scientific development. The purpose of this paper is to present a descriptive and explanatory view of the role of theory in scientific production component; achieve notions establish logical and reasonable theory of why we employ in our investigations, or even - more - why or submit to generate contrast, is one of the great journeys that every researcher must perform. Hence, for a researcher to understand the scientific processes must recognize the purpose and value of theory in research, he is the same one that generates or has a good chance to evaluate.